(untitled) (Research, Society and Development, 2023)
The aim of this study is to learn about the experience of social workers in the Out-of-Home Treatment Program (OHT), with an emphasis on the care of traumatic-orthopedic patients at the Regional Hospital of the Lower Amazon of Pará, Dr. Waldemar Penna - HRBA, in Santarém/PA. This is a qualitative, cross-sectional study with a descriptive approach, based on the theory of historical-dialectical materialism; the sample consisted of 06 Social Workers from the HRBA; a semi-structured interview with open questions was used as the data collection instrument; the data collected was analyzed qualitatively using Bardin’s content analysis. At first, there was a brief discussion about public health and its constitution as a social policy; the second section discusses the TFD in the context of the Unified Health System, and finally presents the main results of the research carried out within the scope of the Multiprofessional Residency in Health - Comprehensive Care in Orthopedics and Traumatology, highlighting the difficulties and challenges imposed on the work of the social worker, such as requests from the team that are incompatible with their professional competencies/attributions; precariousness of the TFD services; difficulties in working with the municipalities where the patients come from; lack of knowledge on the part of traumatology and orthopedics users about the rights and services recommended by the TFD Program, among others. In addition, it is important to lay the foundations for public policies that aim to improve the TFD and bring benefits both to users and to the work of health professionals, especially social workers, who must strengthen the category in the face of the challenges posed by day-to-day work.